Abnormal neutrophil scattergram obtained using Pentra MS CRP in the patients with myelodysplastic syndrome showing dysgranulopoiesis. (3rd September 2015) - Inaba, T.; Ishizuka, K.; Yuasa, S.; Mishima, N.; Ogura, K.; Saito, K.; Kohno, T.; Fujitomo, Y.; Nakanishi, M.; Fujita, N.
Summary: Introduction: Pentra MS CRP is an automated hematology analyzer capable of cytochemistry using Chlorazol black E, a lipid‐staining agent, for white blood cell (WBC) differentials. Pentra MS CRP displays a WBC scattergram according to the cell volume obtained using flow impedance and light absorbance reflecting the Chlorazol black E (CBE)‐positive lipid content. Method: Neutrophil scattergrams obtained using Pentra MS CRP were compared between 5 patients with myelodysplastic syndrome (MDS) and normal controls. Sudan black B (SBB)‐staining patterns of peripheral blood neutrophils were subdivided into four types (types I, II, III, and VI) based on their staining intensity and scored by counting 200 cells. Such SBB scores were also compared between the two groups. Results: Neutrophil scattergrams deviated downward in the MDS group, suggesting the decreased CBE positivity that seemed reflect the reduction of the lipid content in dysplastic neutrophils. SBB scores determined in this study were also decreased in the MDS group when compared with those in normal controls. Conclusion: Pentra MS CRP might rapidly generate useful information on dysplastic neutrophils in patients with MDS based on its cytochemistry for WBC differentials during routine laboratory hematology.